A reestruturação produtiva e o trabalho dos motoristas de caminhão: um estudo de caso em duas empresas de transporte rodoviário de carga - Oliveira, Daniela Barboza de (2012)
The present study has for objective to identify effects of the productive reorganization in the work of truck drivers, in the period between 1980 and 1990 in Brazil. This research is a study of case about two companies of road haulage (RH), with tradition in the segment. They had been selected on the basis of the time of performance in the market, regions of operation and localization of the company. Following criteria defined previously, involving mainly the work time, drivers (salary earning and aggregate) and managers of different areas had been interviewed with a focus on trajectory of work within the company. Beyond the study of case, the bibliographical research on the history of the RH in Brazil contributed to understand the moment the road haulage becames predominant in the country and why. The results show that, historically, the road transport always was connected to the industrial sector and that the changes in the management of the production of this sector had direct impact in the management of the transports. Thus, since the 1990s, the transporters have increased the agility of the process of transport, reduced costs and time spent, guaranteeing the quality of the services given through the use of concepts and practices linked to Suplly Chain Management (SCM) and Logistics. New practices in an old labor model: new employment contracts to reduce costs and avoid the limitations of labor law (outsourcing), extension of working hours and remuneration for productivity (to drive more is to earn more). The absence of an adequate legislation that regulates the activities of the RH and imposes limits to the drive time and distinguishes it and the work time, equally contributes to the long labor journey to become one more factor of risk in this profession, especially between the drivers who work with fast orders lines.